Bronze Age Mediterranean Island Cultures and the Ancient Near East - Knapp, A. Bernard (The Biblical archaeologist, 1992)
In the conclusion of a two-part article on factors that led to the colonization of the Mediterranean islands, developments in the Aegean are rounded out with a brief look at the Neo-Palatial period, an overview of the Middle-Late Bronze Age on Thera, and an examination of the Post-Palatial period, when Minoan power and influence in the Aegean finally disappeared. Other areas studied extensively include the island of Rhodes during the Bronze Age, the association of Rhodes with the Aḫḫiyawa, the role played by the trade in metals during the Bronze Age, and the elusive peoples known as the Shardanu.